Prelude to Casablanca: British Operational Planning for Metropolitan Italy and the Origins of the Allied Invasion of Sicily, 1940–1941. (November 2019) - Aterrano, Marco Maria
The article seeks to reassess the British focus on 'knocking Italy out of the war' and the way it shaped political and military discussions in London long before the American ally joined the combined planning. Between 1940 and 1941 Britain planned four major military operations having Italy as their main target. This complex process drove a wedge between an aggressive prime minister and a more conservative planning staff. A clear separation between a minimalist and a proactive stance marked the entire process, highlighting the existence of a sharp divide within the British planning establishment.